Molecular Characterization and Biological Function of a Novel LncRNA CRNG in Swine - Lu, Qirong; Li, Li; Huang, Aixin; Cui, Luqing; Zhang, Yinfeng; Liu, Qianying; Wang, Xu; Wang, Yulian; Liu, Zhenli; Yuan, Zonghui; Dai, Menghong (Frontiers in Pharmacology, 2019)
Our previous study has showed that a novel gene is differentially expressed in the liver of cyadox-fed piglets, but its sequence and function are unknown. Here, rapid amplification of cDNA ends (RACE) and bioinformatics analysis showed that the novel gene is 953 bp without protein-coding ability and locates in chromosome 11. Hence, we identified the novel gene as long noncoding RNA (lncRNA) and named it cyadox-related novel gene (CRNG). Fluorescence in situ hybridization (FISH) showed that CRNG mainly distributes in cytoplasm. Moreover, microarray assay in combination with CRNG interference and overexpression showed that the differential genes such as ANPEP, KITLG, STAT5A, FOXP3, miR-451, IL-2, IL-10, IL-6, TNF-α are mainly involved in viral and pathogens infection and the immune-inflammatory responses in PK-15 cells. This work reveals that CRNG might play a role in preventing the host from being infected by pathogens and viruses and exerting immune regulatory effects in the cytoplasm, which may be involved in prophylaxis of cyadox in piglets.